Experimental and computational exploration of the UV-visible properties of hexaniobate and hexatantalate ions1. Issue 10 (6th February 2015) - Deblonde, Gauthier J.-P.; Moncomble, Aurélien; Cote, Gérard; Bélair, Sarah; Chagnes, Alexandre
<x xml:space="preserve">Abstract</x> The UV-visible properties of hexaniobate (HxNb6O19x−8) and hexatantalate (HxTa6O19x−8) ions were investigated experimentally and by DFT calculations.